2021
DOI: 10.1002/adma.202101757
|View full text |Cite
|
Sign up to set email alerts
|

Powering Electronic Devices from Salt Gradients in AA‐Battery‐Sized Stacks of Hydrogel‐Infused Paper

Abstract: Strongly electric fish use gradients of ions within their bodies to generate stunning external electrical discharges; the most powerful of these organisms, the Atlantic torpedo ray, can produce pulses of over 1 kW from its electric organs. Despite extensive study of this phenomenon in nature, the development of artificial power generation schemes based on ion gradients for portable, wearable, or implantable human use has remained out of reach. Previously, an artificial electric organ inspired by the electric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The circuit schematic (Figure S7, Supporting Information) has successfully lights up “UESTC” LEDs instantly by the new 3D capacitors at different voltages (≈400–1000 V) ( Figure a). [ 56 ] The equivalent insulation resistance can reach ≈5 GΩ at 600 V (Figure 4b), which could be ascribed to the amorphous wide bandgap structure of the glass and the low roughness of the porous inner wall. The complex‐plane impedance spectrum reveals an equivalent series resistance (ESR) of ≈2920 ohms (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…The circuit schematic (Figure S7, Supporting Information) has successfully lights up “UESTC” LEDs instantly by the new 3D capacitors at different voltages (≈400–1000 V) ( Figure a). [ 56 ] The equivalent insulation resistance can reach ≈5 GΩ at 600 V (Figure 4b), which could be ascribed to the amorphous wide bandgap structure of the glass and the low roughness of the porous inner wall. The complex‐plane impedance spectrum reveals an equivalent series resistance (ESR) of ≈2920 ohms (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, although the mimicking structure remained the same, NaCl was replaced by LiCl. 41 The maximum power density of 1.8 W/m 2 obtained by Guha et al 41 was 67 more than with NaCl by Schroeder et al, 31 and the improved system was able to power 3 LEDs in series.…”
Section: Biomimetic Electricity Generationmentioning
confidence: 89%
“…23,27,45 We have previously demonstrated that the composition of ionic species in salinity gradient power sources impacts the resulting power density. 38,50 Here, we directly compare different CC solvents (MEA, DEA, MDEA, AMP, and ammonia) in the same labscale CCRED device and demonstrate that ammonia achieved the highest power density, reaching nearly 1 W m −2 cell −1 . Ultimately, these results suggest that CCRED could potentially contribute to economically motivating adoption of CC technology.…”
Section: Introductionmentioning
confidence: 95%
“…When using different CC solvents, the reaction with CO 2 produces different ionic species; sterically hindered amines become protonated and CO 2 forms bicarbonate with water molecules, whereas unhindered amines (MEA and DEA) react directly with CO 2 to form carbamates in addition to generating protonated species and bicarbonate (eqs –). ,, We have previously demonstrated that the composition of ionic species in salinity gradient power sources impacts the resulting power density. , Here, we directly compare different CC solvents (MEA, DEA, MDEA, AMP, and ammonia) in the same lab-scale CCRED device and demonstrate that ammonia achieved the highest power density, reaching nearly 1 W m –2 cell –1 . Ultimately, these results suggest that CCRED could potentially contribute to economically motivating adoption of CC technology.…”
Section: Introductionmentioning
confidence: 99%